The impact of fetal alcohol syndrome on a child's classroom performance : a case study of a rural South African school - Lubbe, Melissa (School of Economics, 2016)
Fetal Alcohol Syndrome (FAS) is the most severe of a spectrum of birth defects caused by a mother drinking alcohol whilst pregnant. Its manifestation in the Central Nervous System causes intellectual and behavioural abnormalities, which pose considerable challenges in the classroom. This case study explores the classroom environment and educational outcomes of learners with FAS in a rural South African school. The study was conducted at Elizabethfontein Primary School (EFPS), a farm school near Clanwilliam in the Western Cape. The sample comprises of all 170 learners in Grade 1 to Grade 4. A prevalence rate of FAS of 124 per 1000 (12.4%) was found. EFPS is a Quintile 1 school that relies heavily on fundraising (especially in the form of Riel Dancing) and sponsorship to afford extra staff (such as Koshuis Tannies and teaching assistants), maintenance and transportation of learners. The lack of Grade R school preparation and the environment learners grow up in results in discipline problems, many learners repeating, being progressed before they are ready and a high dropout rate. Child abuse and neglect is common today, prompting the EFPS boarding house to act as "safe haven" during the week for two thirds of its learners. The school provides security, routine and constant meals (as part of the School Nutrition Program and supplemented by the school garden). Data on educational outcomes was collected through participant observation (classroom behaviour), collection of information from existing sauces (Home Language Marks and Mathematics Marks) and collection of new data (Reading Score). A physician diagnosed those children with FAS using a three-stage process. Having FAS is associated with lower home language marks ( 2.8 to 8.55 percentage points) and behavioural scores (1.73 to 4.21 percentage points). The mitigating effect of the school on FAS learners might have reduced the impact of FAS. Children with FAS struggle academically and in following rules and principles as they have lower intellectual capabilities and cannot generalise from one situation to the next. Memory deficits, especially verbally and visuospatially, present challenges in following instructions and copying from the board. Children with FAS are also hyperactive, distractible and inattentive, which causes classroom disruptions and pose a negative externality to other learners. They find it difficult to follow social cues, but want to be helpful and well liked, making children with FAS vulnerable to manipulation. Strategies for intervention have been explored by specialised schools and studies, but must be translated into viable options for the mainstream under-resourced classroom. In order to develop appropriate strategies for classroom intervention a comprehensive understanding of FAS in this context must first be established. Many learners are isolated by a lack of tarred roads and cell phone reception within the large catchment area of EFPS. As descendants of local tribes and slaves the history of this farming area still influences them today. The legacy of the Dop system can still be seen, as alcohol forms a cornerstone of social interactions, especially in binge drinking over weekends, which exposes children to the cycle of alcohol addiction from a young age. Racial segregation and the impact of Apartheid have influenced the educational trajectory of coloured children. The value of this study lies in the in-depth insight into the context learners find themselves in, and the specific challenges associated with FAS learners. Future studies can build on the methodology and explore ways to improve the lives of children with FAS. Research must be interdisciplinary and in collaboration with the community. In response to this research EFPS has declared 2016 as "The Year of Alcohol Awareness" . Intervention strategies must be aimed towards these isolated, under resourced communities.